Impact of connecting tuberculosis directly observed therapy short-course with smoking cessation on health-related quality of life - Awaisu, Ahmed; Nik Mohamed, Mohamad Haniki; Mohamad Noordin, Noorliza; Muttalif, Abdul Razak; Abd Aziz, Noorizan; Syed Sulaiman, Syed Azhar; Ahmad Mahayiddin, Aziah (BioMed Central, 2012)
Background: With evolving evidence of association between tuberculosis (TB) and tobacco smoking,recommendations for the inclusion of tobacco cessation interventions in TB care are becoming increasingly important and more widely disseminated. Connecting TB and tobacco cessation interventions has been strongly advocated as this may yield better outcomes. However, no study has documented the impact of such connection on health-related quality of life (HRQoL). The objective of this study was to document the impact of an integrated TB directly observed therapy short-course (DOTS) plus smoking cessation intervention (SCI) on HRQoL.